Anogenital Warts in Childhood – Always a Marker for Sexual Abuse? - Bussen, S.; Sütterlin, M.; Schmidt, U.; Bussen, D. (Geburtshilfe und Frauenheilkunde, 2012)
Human papilloma viruses (HPV) are common pathogens associated with a wide range of cutaneous and mucosal infections in childhood. Different HPV types can cause common warts and anogenital warts. Condylomata acuminata in children may be, but are not necessarily, an indicator of sexual abuse. Each individual case therefore requires careful examination, with consideration of other possible means of transmission. Diagnosis of anogenital warts is generally by means of clinical examination. Additional histological, serological or molecular genetic investigation may be indicated occasionally. The high rate of spontaneous remission and the rate of recurrence after treatment should be considered. The available topical and surgical treatment options are discussed.
Keywords: condylomata acuminata; genital warts; HPV infection; sexual abuse